(untitled) (Scientific journal of the Fergana State University, 2024)
This article explores the use of shifonemas (or shifonyms), medicinal plant names as phraseological units related to the period of youth. Plants are an essential part of human life, and they have been used for various purposes since ancient times. In addition to their medicinal and nutritional values, plants have also been used as symbols in literature, art, and culture. The use of phytonyms, shifonemas as phraseological units is a common phenomenon in many languages. These phraseological units are used to express various emotions, feelings, and experiences related to different stages of life.